Meta-assessment in a project-based systems engineering course. Issue 4 (19th May 2017) - Wengrowicz, Niva; Dori, Yehudit Judy; Dori, Dov
Abstract : Project-based learning (PBL) facilitates significant learning, but it poses a major assessment challenge for assessing individual content knowledge. We developed and implemented an assessment approach and tool for a mandatory undergraduate systems engineering PBL-based course. We call this type of assessment student - oriented meta-assessment. Research participants included 131 undergraduate engineering students who carried out team projects requiring conceptual modelling of complex systems. Next, individual students assessed their peer team projects. Finally, the course staff assessed students individually, based on the content knowledge that was reflected in students' comments to their peers, by using the new meta-assessment tool. The research findings validated the meta-assessment tool which can serve for assessing various PBL courses. Our contribution is twofold: a new approach for assessing project-based undergraduate engineering courses, and classification of meta-assessment methods into three types, where a student-oriented meta-assessment as one of the three meta-assessment methods is our newly introduced and validated method.